Characterisation of aluminium alloy tubes filled with aluminium alloy integral-skin foam under axial compressive loads. (March 2015) - Duarte, Isabel; Krstulović-Opara, Lovre; Vesenjak, Matej
Abstract: Novel ex-situ foam-filled tubes (FFTs) were prepared by inserting an integral-skin foam filler into an empty aluminium alloy tube. The aluminium alloy foam filler is prepared by powder compact foaming technique allowing to combine the Al-alloy integral-skin filler with an Al-alloy tube which has not been studied yet. Axial compressive crush performance of the individual components (empty tubes and integral-skin foams) and FFTs was studied and evaluated using uniaxial compression tests, exploring their deformation and failure mechanisms. The FFTs deform by axisymmetric axial crushing mode (concertina mode) with the formation of a single visible concertina fold, but with the formation and propagation of longitudinal cracks. The results confirm an improved crush performance under axial compressive loads by introducing the integral-skin foam as a filler in empty tubes.